2011
DOI: 10.1038/pr.2011.913
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Score Identifies NICU Patients with Gram-Negative Bacteremia

Abstract: Background: Gram-negative late-onset neonatal sepsis has high mortality, but initial antibiotic regimens may not cover these most virulent pathogens. While heart rate characteristics (HRC) monitoring can lead to early sepsis diagnosis, other non-infective conditions elevate the HRC index, or HeRO score. Since a recent randomized trial showed reduced mortality with HeRO monitoring, we expect its use to increase. Cytokine levels rise in response to systemic inflammation and sepsis, and patterns of expression mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Animal studies in both prenatal and postnatal models have shown that pathogen toxins such as lipopolysaccharide from Escherichia coli can dampen heart rate variability, in part through pro-inflammatory cytokines [23,24]. In a study of 226 infants at two NICUs undergoing evaluations for suspected late-onset sepsis, there was an association between elevated plasma cytokines, an elevated HRC index (reflecting low heart rate variability), and growth of bacteria in blood culture, particularly in cases of Gram-negative septicemia [25].…”
Section: Mechanisms Of Abnormal Heart Rate Characteristics In Sepsismentioning
confidence: 98%
“…Animal studies in both prenatal and postnatal models have shown that pathogen toxins such as lipopolysaccharide from Escherichia coli can dampen heart rate variability, in part through pro-inflammatory cytokines [23,24]. In a study of 226 infants at two NICUs undergoing evaluations for suspected late-onset sepsis, there was an association between elevated plasma cytokines, an elevated HRC index (reflecting low heart rate variability), and growth of bacteria in blood culture, particularly in cases of Gram-negative septicemia [25].…”
Section: Mechanisms Of Abnormal Heart Rate Characteristics In Sepsismentioning
confidence: 98%
“…In premature infants, TLR-4 levels remain elevated, leading to enterocyte apoptosis followed by bacterial translocation of gram-negative bacteria through the intestinal mucosa.In addition to the model of development of innate immune responses, a specific role belongs to the peculiarities of the development of the intestinal microvessels and the state of the microbiota, in particular, the impact of antibacterial therapy on its formation. It is proved that the onset of the disease most often falls at the post-conceptual age of 29-32 weeks of pregnancy[6].Based on this, the aim of the study was to assess the relationship of anamnestic,clinical and paraclinical data with the course of NEC in premature infants undergoing inpatient treatment in the neonatal unit of Regional Children's Clinical Hospital (RCCH) of Chernivtsi. Materials and method.…”
mentioning
confidence: 99%